Direct visual servoing and interaction control for a two-arms on-orbit servicing spacecraft - Ramón, José Luis; Pomares, Jorge; Felicetti, Leonard (Elsevier, 2021)
A direct visual-servoing algorithm for control of a space-based two-arm manipulator is proposed in this paper. The algorithm can be utilized in a two-arm manipulators configuration, where one of the arms performs the manipulation and the second arm is dedicated to the observation of the target zone of manipulation. The algorithm utilizes both visual features extracted from onboard cameras and force and torque measured at the manipulator's end-effector to control the movements of the manipulator during on-orbit servicing operations. The algorithm takes into account the relative dynamics of the bodies involved, it relies on images taken independently from de-localized cameras, e.g. at the end-effector of a second manipulator, and it integrates an impedance control for the compensation of eventual contact reactions when the end effector touches and operates the target body. The analytical derivations demonstrate the stability of the algorithm and incorporate an impedance compliance strategy into an optimal framework formulation. Simulations results in two different scenarios have been presented to show the adequate behavior of the presented approach in on-orbit-servicing operations.
Keywords: Visual servoing; Space manipulator; Interaction control